Brimonidine gel 0.33% rapidly improves patient‐reported outcomes by controlling facial erythema of rosacea: a randomized, double‐blind, vehicle‐controlled study. (28th September 2015) - Layton, A.M.; Schaller, M.; Homey, B.; Hofmann, M.A.; Bewley, A.P.; Lehmann, P.; Nohlgård, C.; Sarwer, D.B.; Kerrouche, N.; Ma, Y.M.
Abstract: Background: Facial redness contributes to impaired psychosocial functioning in rosacea patients and the only approved treatment for erythema is topical brimonidine gel 0.33%. Objectives: To evaluate patient‐reported outcomes, as well as efficacy and safety, in subjects with self‐perceived severe erythema treated with brimonidine gel 0.33% compared to vehicle. Methods: An 8‐day multicenter, randomized study comparing once‐daily brimonidine gel 0.33% with vehicle gel using a facial redness questionnaire, subject satisfaction questionnaire and a patient diary of facial redness control to assess patient‐reported outcomes. Results: Of the 92 included subjects with self‐perceived severe erythema, very few were satisfied with their appearance at baseline (4.2% brimonidine group, 0 vehicle group). On Day 8, significantly more brimonidine group subjects were satisfied with their facial appearance compared to vehicle group (36.9% vs. 21.5%; P < 0.05), with the overall treatment effect (69.6% vs. 40.4%; P < 0.01), and with the improvement in their facial redness (67.4% vs. 33.3%; P < 0.001). More brimonidine group subjects were able to control their facial redness daily (e.g. 83.0% vs. 38.9% on Day 1). On Day 8, significantly more brimonidine group subjects than vehicle group had at least a one‐grade improvement from baseline in the Clinician Erythema Assessment score (71.7% vs. 35.7%; P = 0.0011) and Patient Self‐Assessment score (76.1% vs. 47.6%; P = 0.004). More subjects in the brimonidine group (29.2%) reported treatment‐related adverse events than in the vehicle group (15.9%) but most were mild and transient. Conclusions: Once‐daily brimonidine gel 0.33% allowed patients to rapidly control their facial redness and significantly improved patient‐reported outcomes in the treatment of persistent facial erythema of rosacea.